Conservation Reserve Program Grasslands and Ring-Necked Pheasant Abundance in Minnesota - James F. Drake; Richard O. Kimmel; J. David Smith; Gary Oehlert (National Quail Symposium Proceedings, 2017)
Ring-necked pheasant (Phasianus colchicus) abundance was measured on 15 study areas using roadside counts during the summers of 1990-1994 to examine possible relationships to permanent grasslands and 9 other cover types. The majority of permanent grasslands was enrolled in the Conservation Reserve Program (CRP) and likely would have been actively used for agriculture if not for the CRP. Roads were divided into 300 m segments and the proportion of each cover type was determined within 200 m and 800 m of each segment. A non-parametric procedure was used to determine the most significant predictors of number of pheasants observed on each road segment during roadside surveys. Year, study area, and proportion of cover type were used as predictor variables. Proportion of permanent grassland cover was the most significant predictor in every model examined. Numbers of pheasants, predominantly broods, were approximately 10 times higher in samples that had >30% grassland compared to samples with ≤ 10%. There was no statistically significant increase in number of pheasants as grassland increased from 30 to 100%. Year-to-year variation and differences among study areas were the second most significant factors in predicting the number of pheasants observed. Small grains and pasture were also positively correlated to pheasant numbers. If CRP grassland had not been available, pheasant abundance would have been significantly lower in the study areas.
Keywords: broods; Conservation Reserve Program; formal inference-based recursive modeling (FIRM); GIS; habitat; Minnesota; Phasianus colchicus; ring-necked pheasant